Characterization and functional analysis of chicken hnRNP protein - Ke Wang; Manzi Huang; Qinghua Zeng; Huansheng Wu (Poultry Science)
While the role of hnRNP proteins in modulating interferon signaling and virus replication in mammals has been extensively studied, the impact of chicken hnRNPs on innate immune response and Infectious Bursal Disease Virus (IBDV) replication remains largely unexplored. In this study, multiple chicken hnRNPs were identified to interact with genomic dsRNA. Initially, these hnRNPs were found to be exclusively localized in the nucleus before IBDV infection. However, post-infection, they translocated into the cytoplasm to co-localize with the viral dsRNA. Furthermore, the effects of various chicken hnRNPs on IFN-β activation, induced by the chicken MDA5-MAVS-TBK1 and STING-IRF7 pathway, were analyzed. Among these hnRNPs, hnRNPA3 demonstrated the most significant reduction in inhibiting IFN-β activation at the MAVS step. Additionally, overexpression of chicken hnRNPA3 was found to markedly enhance IBDV replication. Conversely, silencing chicken hnRNPA3 via siRNA significantly increased IFN-β production, thereby substantially suppressing IBDV replication. In summary, our findings reveal for the first time that multiple chicken hnRNPs interact with viral dsRNA, modulate IFN-β production, and specifically, that chicken hnRNPA3 promotes IBDV replication. These insights into the role of chicken hnRNPs in viral replication and immune response could pave the way for new therapeutic strategies against IBDV.